Honey production and its externality effects - Árváné Georgina, Ványi; Csapó, Zsolt; Kárpáti, László; Nábrádi, András (Economics of Agriculture, 2010)
Bee-keeping and honey production has a long history in Hungary. The honey production has important role in rural life. It is confirmed by researchers studies that plant pollination by honey bees has significant positive external impacts on potential yields in orchards. Although the contribution of honey production to the GDP in Hungary is only a few per cent, other benefits play a more important role. This paper focuses on secondary research methods, gathering and evaluating figures regarding the positive external impacts of plant pollination by honey bees as well as finding possible solution for the problem that bee-keepers have a lot of costs in connection with carrying honey bees to orchards, while farmers "only" benefit from the positive externality of plant pollination in their fields. To evaluate its economic effects a numerical HEEM-model was developed and applied for the Hungarian situation. The financial outcome of the bee-keeping sector contributes considerably to the rural development in Hungary.